2013
DOI: 10.1177/1060028013514375
|View full text |Cite
|
Sign up to set email alerts
|

MenHibrix

Abstract: Hib-MenCY-TT has been demonstrated to be a safe and immunogenic vaccination for prevention of disease caused by N meningitidis serogroups C and Y and H influenzae type b in healthy infants and toddlers. Currently, the ACIP recommends the use of Hib-MenCY-TT specifically in high-risk infants aged 6 weeks to 18 months. Hib-MenCY-TT provides the first therapeutic option for vaccination of infants as young as 6 weeks of age who are at increased risk for meningococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…All 22 macaques also received separate i.m. injections of a control, licensed polysaccharide-protein conjugate vaccine ( Haemophilus influenzae type b– Neisseria meningitidis serogroups C and Y – tetanus toxoid, referred to herein as Hib-MenCY-TT) (29) in the other leg. Four additional infant macaques (2 with FH that bound strongly to FHbp and 2 with FH that bound weakly) served as negative controls and were immunized with aluminum hydroxide alone in one leg and saline in the other leg, which corresponded to the adjuvant in the FHbp vaccine and the diluent for the non-adjuvated Hib-MenCY-TT vaccine, respectively (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…All 22 macaques also received separate i.m. injections of a control, licensed polysaccharide-protein conjugate vaccine ( Haemophilus influenzae type b– Neisseria meningitidis serogroups C and Y – tetanus toxoid, referred to herein as Hib-MenCY-TT) (29) in the other leg. Four additional infant macaques (2 with FH that bound strongly to FHbp and 2 with FH that bound weakly) served as negative controls and were immunized with aluminum hydroxide alone in one leg and saline in the other leg, which corresponded to the adjuvant in the FHbp vaccine and the diluent for the non-adjuvated Hib-MenCY-TT vaccine, respectively (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…2 The combined Hib, MenC and MenY tetanus toxoid (TT) conjugate vaccine (Hib-MenCY-TT, MenHibrix, GSK) was developed to protect infants against invasive diseases caused by Hib, MenC and MenY without increasing the number of injections in the US immunization schedule and was approved by the Food and Drug Administration in 2012 for use in infants as a 4-dose vaccination series. 6,7 A previous phase III study showed that a 3-dose primary vaccination series with Hib-MenCY-TT in infants at 2, 4 and 6 months of age followed by a 4th dose at 12-15 months of age had a comparable immunogenicity profile to licensed Hib vaccines, induced a robust immune response against MenC and MenY, and had a clinically acceptable safety profile. 7,8 In addition, Hib-MenCY-TT did not appear to interfere with the immune responses of the concomitantly administered diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus vaccine (DTaP-HBV-IPV), 7-valent pneumococcal conjugate vaccine, 9,10 mumps-measles-rubella vaccine, and varicella virus vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A previous phase III study showed that a 3-dose primary vaccination series with Hib-MenCY-TT in infants at 2, 4 and 6 months of age followed by a 4th dose at 12-15 months of age had a comparable immunogenicity profile to licensed Hib vaccines, induced a robust immune response against MenC and MenY, and had a clinically acceptable safety profile. 7,8 In addition, Hib-MenCY-TT did not appear to interfere with the immune responses of the concomitantly administered diphtheria-tetanus-acellular pertussis-hepatitis B-inactivated poliovirus vaccine (DTaP-HBV-IPV), 7-valent pneumococcal conjugate vaccine, 9,10 mumps-measles-rubella vaccine, and varicella virus vaccine. 11 This study evaluated the immunogenicity and safety of coadministered Hib-MenCY-TT with the remaining routinely administered concomitant vaccines (human rotavirus vaccine [HRV; Rotarix, GSK] and hepatitis A vaccine [HAV; Havrix, GSK]) and with the currently available 13-valent pneumococcal conjugate vaccine (PCV13; Prevnar, Pfizer).…”
Section: Introductionmentioning
confidence: 99%